Teachers’ need analysis in STEM-Eco-Mathematics learning: Evidence from border elementary schools - Yosua Damas Sadewo; Totok Victor Didik Saputro; Candra Gudiato; Andriano Andriano; Feny Rita Fiantika; Sabariah Sabariah; Falenthino Sampouw; Nurselam Hassen (Universitas Papua, 2026)
The integration of STEM with the environmental context is increasingly important as mathematics education emphasizes authentic, and interdiciplinary learning experiences. However, empirical evidence on the learning needs of elementary school teachers in boarder area is limited. This study examines the needs of teachers in implementing STEM-Eco-Mathematics learning in elementary schools in Bengkayang, an Indonesia-Malaysia border area. Data were collected from 70 elementary school teachers via online questionnaire comprising 20 Likert-scale statements representing five dimension, namely innovative learning modeling, STEM integration, contextual learning, mathematical modeling, and teacher readiness. The data were analyzed using descriptive statistics. The results showed that teachers had a high level of need for implementing STEM-Eco-Mathematics (M= 3.57; SD = 0.52). The highest needs were found in innovative learning models, STEM integration, and contextual learning while mathematical modeling and teacher readiness received relatively lower scores. Although teachers have recognized the importance of intediciplinary and context-based mathematics learning, they still need pratical support to apply this approach effectively in everyday learning. These findings emphasize the importance of professional development programs and the development of leaning models that are responsive to the characteristics of border areas to strengthen teachers’ capacity to implement STEM-Eco-Mathematics effectively..